Diverse Structures Based on a Heptanuclear Cobalt Cluster with 0D to 3D Metal–Organic Frameworks: Magnetism and Application in Batteries. Issue 8 (4th January 2018) - Qin, Bo‐Wen; Huang, Ke‐Cheng; Zhang, Yu; Zhou, Lei; Cui, Zheng; Zhang, Kuo; Zhang, Xiao‐Ying; Zhang, Jing‐Ping
Abstract: Polymetallic complexes with interesting multifunctions have attracted extensive investigation. Synthesized through the use of different cobalt salt anions and solvents, five complexes, namely [Co II 4 Co III 3 (H2 L)3 Cl5 (MeOH)] (1 ), [Co II 4 Co III 3 (H2 L)3 (CH3 COO)4 (HCOO)⋅ H2 O] n (2 ), [Co II 4 Co III 3 (H2 L)3 (HCOO)4 (NO3 )⋅ 2H2 O] n (3 ), [Co II 4 Co III 3 (H2 L)3 (bda)(CH3 COO)4 ⋅ 2H2 O] n (4 ), and [Co II 4 Co III 3 (H2 L)3 (ipa)(HCOO)3 (dmf)⋅ H2 O] n (5 ) (H6 L=bis‐tris propane; BDA=biphenyl‐4, 4′‐dicarboxylic acid; IPA=isophthalic acid; DMF= N, N ‐dimethylformamide), based on the heptanuclear Co II 4 Co III 3 cluster with structures from 0D to 3D metal–organic frameworks (MOFs) have been solvothermally synthesized. Compound1 is the first 0D heptanuclear cluster based on H6 L. Compound2 crystallizes in the chiral space group P 21 21 21 and consists of a 1D chiral helical chain. Complex3 exhibits a 3D network structure. Compound4 possesses a 1D zigzag‐like chain structure. Finally, compound5 was obtained as a 3D microporous structure. Compounds1, 3, and4 display dominant ferrimagnetic interactions whereas compounds2 and5 exhibit antiferromagnetic interactions. Moreover, the Co3 O4 prepared by calcining compound2 presents a reversible capacity of 1122.9 mA h g −1 at 0.2 A g −1 after 100 cycles and an excellent rate capability, which suggests that coordination compounds with a 1D chain structure are outstanding precursors for preparing anode materials for lithium ion batteries. Abstract : Tuning cluster structures . Five complexes based on the heptanuclear Co II 4 Co III 3 cluster with structures from 0D to 3D metal–organic frameworks (see figure) have been synthesized and their potential applications in magnetism, batteries with high reversible capacity and excellent rate capability, reversible iodine adsorption, and heterogeneous catalysis have been explored.